2011
DOI: 10.1016/j.jmarsys.2011.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Modeling waves, currents and sandbars on natural beaches: The effect of surface rollers

Abstract: A morphodynamic model has been extended to gain more fundamental knowledge about the formation of nearshore sand bars. The model describes feedbacks between waves, rollers, depth-averaged currents and bed evolution, so that self-organized processes can develop. Offshore wave, wind and tide conditions and the bathymetry measured at Egmond site (the Netherlands) are firstly applied to compute the longshore current and wave height profiles. A comparison of the results with field data of that beach reveals that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…The values of γ b and k a were adjusted so that the profiles of H o and V o could be modeled with the minimum RMS error. The default values of β rol and M were chosen for being standard widely used values, and they were subsequently shown to give nearly the smallest RMS errors of H o and V o [ Ribas et al , 2011]. An example of measured and modeled H o and V o on 18 October 1998 at Egmond beach (when the wave conditions were similar to those of the default case of the present study) is shown in Figure 3.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of γ b and k a were adjusted so that the profiles of H o and V o could be modeled with the minimum RMS error. The default values of β rol and M were chosen for being standard widely used values, and they were subsequently shown to give nearly the smallest RMS errors of H o and V o [ Ribas et al , 2011]. An example of measured and modeled H o and V o on 18 October 1998 at Egmond beach (when the wave conditions were similar to those of the default case of the present study) is shown in Figure 3.…”
Section: Modelmentioning
confidence: 99%
“…Performing a more quantitative comparison between model results and field observations is the second essential step to test the bed‐flow mechanism and obtain a better understanding of the underlying physical processes. Ribas et al [2011] recently studied the effect of surface rollers on the profiles of the current and scriptC da in the surf zone. They presented a new self‐organization model that included the roller dynamics in the hydrodynamic equations and its effect in the sediment transport.…”
Section: Introductionmentioning
confidence: 99%
“…The default offshore wave conditions (H off = 0.8 m, T p = 9 s, and θ off = 30 o ) are the mean values measured at the Gold coast at the start of the finger bar events (Table 1). The default values of the physical parameters of the model parameterizations are the same that were used in the previous applications of Duck and Noordwijk (Ribas et al 2011a(Ribas et al , 2012 and were a result of a model calibration with data from a Dutch beach close to Noordwijk (Ribas et al 2011b).…”
Section: Methodsmentioning
confidence: 99%
“…These studies showed that accounting for the longshore currents generated by obliquely incident waves and wave rollers (which not only affect the currents but also generate additional sediment resuspension) is essential to successfully explain the formation of finger bars at Noordwijk (Ribas et al 2011b(Ribas et al , 2012 and at Duck (Ribas et al 2011a). A depth-averaged sediment concentration that decreases in the seaward direction together with an offshore deflection of the longshore current over the up-current oriented bars are necessary conditions for the formation of finger bars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation